CHARACTERISTIC CHEMOTHERAPY RESPONSE OF TESTICULAR CANCER PATIENTS IN TERTIARY HOSPITAL - Fabrianta, Dio Mafazi; Seputra, Kurnia Penta; Daryanto, Besut (Indonesian Urological Association, 2022)
Objective: The purpose of this study was to determine the correlation of testicular tumor markers on the success of chemotherapy in my institution. Material & Methods: This research is a retrospective study single center using the medical record database at the span of the research period. The patient with testicular carcinoma who underwent complete chemotherapy between 2017 until 2022 was included. The data collected and analyzed by descriptive data and analytical correlation using SPSS Ver. 25. The comparation test using T-test and Anova. Results: A total of 31 testicular cancer patients were enrolled in the study. Fifteen patients were seminoma and 16 patients were non-seminoma. The mean age of patient at presentation of seminoma and non seminoma were 38.3 ± 17.03 and 30.74 ± 13.01. Most patients presented a karnofsky score about 79 ± 15. There was a negative correlation (r=-0.492) with a significant correlation between the types of testicular carcinoma cases and the response to chemotherapy (p=0.027). There was a significant difference in cases of seminoma and non-seminoma to the success of the chemotherapy response (p=0.024). There was a positive correlation between serum β-HCG, AFP, LDH with serial chemotherapy result with a no significant correlation (p=0.879; p=0.242; and p=0.277). Conclusion: Most types of the testicular carcinoma responses to chemotherapy. Patients with seminoma pathology have better response to chemotherapy compared to non-seminoma.